THE PRIORITY NEED OF ACADEMIC MANAGEMENT OF WATBANGPHLIYAIKLANG SCHOOL BASED ON THE CONCEPT OF INTERACTIONAL COMPETENCIES - Charoensiri, Narisa; Petpon, Ponglikhit (Journal of Educational Review Faculty of Education in MCU, 2025)
The proposes of this research article were to study the need of developing academic management of Watbangphliyaiklang school based on the concept of interactional competencies. This is a Descriptive Research, and the research tool was a questionnaire. Data were collected from 45 samples including school directors and teachers. The data were analyzed by using descriptive statistics of, frequency, percentage, means, and priority needs index modified (PNImodified). The research results were as follows: The overall current of state was at the moderate level and the overall desirable state were at a high level, respectively. The data was analyzed by PNImodified revealed that curriculum development was the most needed (PNImodified = 0.513), followed by learning process development of schools (PNImodified = 0.474) and the measurement and evaluation (PNImodified = 0.461)